Voxar Labs - Teichrieb, Veronica; Simões, Francisco; Figueiredo, Lucas; Lima, João Paulo; Teixeira, João Marcelo; Roberto, Rafael; Da Gama, Alana; Chaves, Thiago; Gomes, Arlindo; Euzébio, Maria (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Voxar Labs is a research group focused in augmenting experiences through research, innovation and collaboration with academia and industry. It develops cutting-edge multi-disciplinary research in the large area of Spatial Computing, tackling the inner areas of Extended Reality, Computer Vision and Natural Interaction. The laboratory aims to create impact through R&D&I, technology transfer, scientific publications, patents and human-resources formation. It is one of the most productive Augmented Reality research groups in the Latin America, also being recognized with seven best papers and ten first-place competitions’ prizes over the nine years of its existence. Voxar Labs is part of the Informatics Center of the Federal University of Pernambuco, located in Recife – Pernambuco, Brazil.